De Novo DNA Synthesis in Aedes aegypti Midgut Cells as a Complementary Strategy to Limit Dengue Viral Replication - Serrato-Salas, Javier; Hernández-Martínez, Salvador; Martínez-Barnetche, Jesús; Condé, Renaud; Alvarado-Delgado, Alejandro; Zumaya-Estrada, Federico; Lanz-Mendoza, Humberto (Frontiers in Microbiology, 2018)
Aedes aegypti is the main vector of Dengue Virus, carrying the virus during the whole mosquito life post-infection. Few mosquito fitness costs have been associated to the virus infection, thereby allowing for a swift dissemination. In order to diminish the mosquito population, public health agency use persistent chemicals with environmental impact for disease control. Most countries barely use biological controls, if at all. With the purpose of developing novel Dengue control strategies, a detailed understanding of the unexplored virus-vector interactions is urgently needed. Damage induced (through tissue injury or bacterial invasion) DNA duplication (endoreplication) has been described in insects during epithelial cells renewal. Here, we delved into the mosquito midgut tissue ability to synthesize DNA de novo; postulating that Dengue virus infection could trigger a protective endoreplication mechanism in some mosquito cells. We hypothesized that the Aedes aegypti orthologue of the Drosophila melanogaster hindsight gene (not previously annotated in Aedes aegypti transcriptome/genome) is part of the Delta-Notch pathway. The activation of this transcriptional cascade leads to genomic DNA endoreplication. The amplification of the genomic copies of specific genes ultimately limits the viral spreading during infection. Conversely, inhibiting DNA synthesis capacity, hence endoreplication, leads to a higher viral replication.